2009
DOI: 10.1038/aja.2009.10
|View full text |Cite
|
Sign up to set email alerts
|

Oncological results, functional outcomes and health-related quality-of-life in men who received a radical prostatectomy or external beam radiation therapy for localized prostate cancer: a study on long-term patient outcome with risk stratification

Abstract: Health-related quality-of-life (HRQOL) after a radical prostatectomy (RP) or external beam radiation therapy (EBRT) has not been studied in conjunction with oncological outcomes in relation to disease risk stratification. Moreover, the long-term outcomes of these treatment approaches have not been studied. We retrospectively analyzed oncological outcomes between consecutive patients receiving RP (n=86) and EBRT (n=76) for localized prostate cancer. HRQOL and functional outcomes could be assessed in 62 RP (79%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…Three thousand three hundred sixty three records were identified, and 25 studies were finally included in this systematic review and meta-analysis [11][12][13][14][15][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Due to a lack of data, 4 studies cannot be meta-analyzed, so we only presented the results of QoL in these studies.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three thousand three hundred sixty three records were identified, and 25 studies were finally included in this systematic review and meta-analysis [11][12][13][14][15][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. Due to a lack of data, 4 studies cannot be meta-analyzed, so we only presented the results of QoL in these studies.…”
Section: Study and Patient Characteristicsmentioning
confidence: 99%
“…Five studies demonstrated that RT performed better in urinary function. Only Takizawa reported there was no difference between RP and RT on urinary function in the high-risk group (P = 0.05) [23]. Three studies showed patients treated with RT had better sexual function than those treated with RP.…”
Section: Health-related Quality Of Lifementioning
confidence: 99%
“…However, lower educational levels, older ages of the spouse, higher incomes and lower tumour stages have been reported to be associated with higher QOL (Song et al , ). Patients who received prostatectomy have been reported to have lower QOL than those treated with radiation therapy or hormone therapy (Krahn et al , ; Takizawa et al , ; Dragicevic et al , ); thus, efforts should be made to enhance the QOL of patients. Based on these findings, we propose that the relevant factors influencing the QOL of patients be identified and an intervention programme be developed in order to enhance the QOL of this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…High quality evidence from contemporary clinical trials comparing radical prostatectomy with radiotherapy, surveillance, brachytherapy or minimally invasive techniques is either lacking or limited (Table 3). [61][62][63][64][65][66][67][68][69] Two early randomized studies compared prostatectomy against radiotherapy, using doses of 40-50 Gy to the whole pelvis with a 20 Gy prostatic boost. 61,62 A significant difference in disease progression was reported in favor of radical prostatectomy, although there was no significant difference in overall survival.…”
Section: Prostatectomy Outcomes Compared To Other Treatment Modalitiesmentioning
confidence: 99%